Social Media and Mental Health Issue among Students during Pandemic Covid-19 - Syiddatul Budury; Andikawati Fitriasari; Diah Jerita Eka Sari (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Covid-19 pandemic makes students studying from home, most of all activity had been doing at home, it makes students having more time to access the social media to update information and to communicate with others. The aim of this research was to analyze the effect of social media to depression, anxiety and stress and self esteem among students. The population is nursing students and the research consist of 118 students, data taken through online system and using Depression Anxiety Stress Scale, Rosenberg Self Esteem and social media using scale. Data was analyzed by pearson correlation test, and the result showed that social media has effect to depression, anxiety and stress occurrence (p-value <0.05) and has no effect to self esteem (>0.05). Using social media have to having screen time to prevent psychosocial problems and social media addiction.